Evolution, suffering, and the creative love of god - Sollereder, B (American Scientific Affiliation, 2016)
In 1859 Charles Darwin uncovered, in The Origin of Species, a world that evolves on the basis of natural selection. The natural world is competitive, violent, and careless of the amount of suffering it produces. Yet, Christian theologians identify God as the creator of the evolutionary process. This raises serious theological questions, including “Why would a good God ordain a process that necessarily involves pain, suffering, and death for so many creatures?” This article will explore the theological implications of evolutionary suffering, and begin to ground a theology of evolutionary creation in the love and work of God.